TELEVISION WEBCAST FRAMING OF THE NIGERIAN GOVERNMENT’S RESPONSE TO BOKO HARAM INSURGENCY IN NORTH-EAST NIGERIA (Singaporean Journal of Business Economics and Management, 2015)
The manner in which international news media discuss contemporary issues on conflict such as the insurgency by Jama' Ahlis Sunna Lidda'awatiwal-Jihad (Boko Haram) in North-East Nigeria has been of concern in media studies. The media is often critical especially of government; with emphasis on their inadequacies, relegating other aspects of their actions. This study sought to comparatively evaluate the framing of government's response to Boko Haram insurgency over three years (2012-2014) on the YouTube webcast channels of: Aljazeera, Cable Network News (CNN), and Channels Television. Adopting the content analysis research design, 157 videos were purposively sampled and analyzed using a validated coding sheet and manual subject Cohen Kappa's inter-coder reliability test which revealed an almost perfect agreement (Kappa Coder 1, 2 & 3: 0.9997, 0.997, and 0.818). Data collected were analyzed using descriptive and inferential statistics. Findings revealed that all three international televisions gave prominence to government's response to Boko Haram insurgency through its Security Agency Operations at 46% on Aljazeera, 36.5% on Channels, and 48.4% on CNN, while the analysis of the yearly trend in their framing presented a significant difference. Aljazeera and CNN adopted a more critical approach in their discourse, while Channels was mostly Distance. The study concluded that television webcast framing of government's response to Boko Haram insurgency in 2012 2014 was of significant difference. It was recommended that foreign international television stations should be more objective and balanced in their framing of government's response to Boko Haram insurgency.